Customers’ Satisfaction and Cause of Satisfaction in Emergency Room, Srinagarind Hospital 2014 - Mitsungnern, Thapanawong; Kotruchin, Praew; Phu-ngoen, Pariwat; Tacha-a-tik, Panor; Prasanson, Tipawan; Sumritrin, Sumana; Lathum, Kalayarat (ศรีนครินทร์เวชสาร, 2015)
Background and objectives: The patient’s satisfaction is an important indicator of Emergency Room (ER) quality that consistent with the 2006 Hospital and Healthcare Standard of The Institute of Hospital Quality Improvement & Accreditation, THAILAND. From past studies, we found many modifiable factors influencing satisfaction including five components e.g. personnel, time, systems, patient characters and place. This study aimed to find level and cause of ER customers’ satisfaction. Leading to service’s quality improvement that match the customers’ need. Materials and Methods: We conducted a descriptive study in customers, who came to ER, Srinagarind hospital during June to November 2014 by simple random selection. Customers answered one self-questionnaire per one visit. in this questionnaires, these were two methods to find levels of satisfaction including Likert and simple descriptive scales. Data were analyzed by descriptive statistics e.g. range, average, ratio, percentage. Results: Overall 101 customers answered questionnaires, their age ranges were between 10-81 year-old, mean age was 35.41 years-old. Thirty two and 69 customers were males and females consecutively. Seventy five were patients (74.26%) who answered by themselves. We evaluated levels of customers’ satisfaction by two methods (100 cases in Likert method, and 88 cases in simple descriptive method). The mean of overall satisfaction were 3.68 out of 5 by Likert method, as similar as 7.72 out of 10 by simple descriptive method. The most satisfaction were the intention of healthcare personnel (33), illness information (15), and ER environment (12), consecutively. On the other hand, the most unsatisfaction were service time (30), communication (9), and ER environment (7), respectively. Conclusion: Customers’satisfaction in ER was minimal to moderate. The most satisfactory factor was intention of healthcare personnel while the most unsatisfactory factor was service time. The result will lead to quality improvement of ER and future research.